Enhancing literacy skills with an emphasis on comprehension in the 21st century - Brewer, Elizabeth (My University, 2012)
This project explored the effectiveness and importance of teaching comprehension strategies through a workshop format. Classroom teachers (n = 6) were surveyed before and after the workshop sessions to assess knowledge and application of comprehension strategies. The pre-survey (survey one) drove the curriculum for each of the five workshop sessions along with State Common Core Standards and district target skills in reading. The teachers and students included in this project were from first (n = 41), second (n = 42), and third (n = 43) grades. Students were assessed using the Developmental Reading Assessment (DRA) and the Common Based Assessment (CBA). Participating teachers were also given a post survey (survey two) to assess the effectiveness of the workshop. Overall, student test scores on the DRA increased after the workshop. Students did not show as much growth on the CBA as with the DRA. Teachers shared their increase in knowledge and ability to teach comprehension strategies through survey two at the end of the workshop. This project emphasized the importance of teaching students research based comprehension strategies and how effective use of these strategies can lead to increased knowledge of a text and stronger performance on formal assessments.
This file was last viewed in Adobe Reader X.
Keywords: Reading comprehension--Study and teaching (Elementary)